1999
DOI: 10.1152/ajpgi.1999.276.1.g249
|View full text |Cite
|
Sign up to set email alerts
|

FGF-2 enhances intestinal stem cell survival and its expression is induced after radiation injury

Abstract: Fibroblast growth factors (FGFs) have mitogenic activity toward a wide variety of cells of mesenchymal, neuronal, and epithelial origin and regulate events in normal embryonic development, angiogenesis, wound repair, and neoplasia. FGF-2 is expressed in many normal adult tissues and can regulate migration and replication of intestinal epithelial cells in culture. However, little is known about the effects of FGF-2 on intestinal epithelial stem cells during either normal epithelial renewal or regeneration of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
76
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 35 publications
7
76
0
Order By: Relevance
“…[29][30][31] Each of these factors has been described earlier as facilitating intestinal mucosa repair, either through enhancement of cell proliferation or inhibition of epithelial cell apoptosis, or by a combination of both. [32][33][34][35] The therapeutic benefit of MSC reported in this study could be the consequence of releases and synergic effects of multiple paracrine factors. Further research is needed to elucidate this complex issue.…”
Section: Discussionmentioning
confidence: 75%
“…[29][30][31] Each of these factors has been described earlier as facilitating intestinal mucosa repair, either through enhancement of cell proliferation or inhibition of epithelial cell apoptosis, or by a combination of both. [32][33][34][35] The therapeutic benefit of MSC reported in this study could be the consequence of releases and synergic effects of multiple paracrine factors. Further research is needed to elucidate this complex issue.…”
Section: Discussionmentioning
confidence: 75%
“…A multistep migratory process of epithelial cells is pivotal to steady-state tissue homeostasis and mucosal protection, since impaired migration often leads to intestinal disorders, including IBD and also neoplasm [26,27]. Although several growth factors may contribute to the multistep processes by stimulating proliferation or maturation of the epithelial cells [21,24,28], the mechanisms regulating hierarchical positioning and in vivo migration of epithelial cells are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] The radioprotective effects of FGF, especially bFGF, on skin and bone marrow in vivo were also documented. [6][7][8][9][10] The present study was the first time to explore the protection by bFGF against radiationinduced proliferation inhibition and apoptotic effects in the splenocytes and thymocytes of mice wholebody X-ray irradiated with 0.5 or 1.0 Gy (clinically relevant doses). We found that bFGF did not provide significant protection when splenocytes and thymocytes were irradiated in vivo and incubated with bFGF in vitro at the current concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…6) Third, bFGF was given in vitro after irradiation in the present study, while previous studies that indicated protective effects were predominantly obtained in in vivo animal studies. 6,7,9,16) For example, Gallicchio et al, 6) demonstrated that when combined with adherent cell-depleted normal murine marrow cells, FGF increased the number of both day 9 and day 12 spleen CFUs from lethally irradiated animals. In adherent cell depleted murine and human marrow cultures, the addition of FGF showed synergistic activity in combination with the optimal concentration of GM-colony-stimulating factor (CSF) for CFU-GM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation